A build-up film sample preparation method and a test method for an FCBGA package substrate
Patent Information
- Application Number
- CN202211393490.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-08
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2042-11-08
AI Technical Summary
薄脆型的增层胶膜材料直接烘烤后容易出现膜厚不均、鼓泡、裁切边缘出现裂纹等现象,在制样和取样过程极易发生断裂
[0036] The FCBGA thickening film of this invention includes a sample preparation method that involves removing the high-temperature-resistant protective layer by pressing before curing the thickening film. During curing, a vacuum laminator is used to complete the sample curing. After curing, the sample is cut using a laser cutting method. Finally, a mechanical peeling machine is used to peel off the film before Young's modulus testing on a DMA (Dielectric-Determining Mechanism). This reduces sample quality problems caused by bubbling, uneven film thickness, difficulty in release, and edge cracks during sampling, and solves the problem of not being able to test Young's modulus using conventional tensile testing machines. Specifically, the results are as follows:
Smart Images

Figure CN118010435B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of semiconductor packaging technology, and specifically to a method for preparing and testing an additive film sample for an FCBGA packaging substrate. Background Technology
[0002] As the integration of semiconductor components increases, the size of packaging substrates continues to shrink, which places higher demands on the thickness and quality of the addendum films used in packaging substrates.
[0003] Before being applied, laminated films typically undergo Young's modulus testing to ensure they meet requirements. Young's modulus is a crucial physical quantity characterizing the deformation and intrinsic relationship of solid materials, describing their resistance to deformation. It reflects the stiffness of a material; a higher Young's modulus indicates a smaller deformation. Besides its application in mechanical component design, Young's modulus is also significant for studying the mechanical properties of various materials such as metals, optical fibers, nanomaterials, semiconductors, polymers, rubber, and ceramics. Based on the motion of the sample being tested, testing methods can be broadly categorized into two types: dynamic testing and static testing. Static testing methods are further divided into two categories based on the material structure: static tensile testing, primarily used for linear structures, and three-point and four-point bending testing, mainly used for surface and columnar structures. Static testing directly determines Young's modulus through the stress-strain relationship. This method not only obtains the Young's modulus but also corresponding parameters such as tensile and flexural strength. Dynamic testing methods include the resonance method and the sound velocity method. The resonance method determines the Young's modulus of a material based on the relationship between the resonant frequency of the specimen and its Young's modulus. The sound velocity method determines the Young's modulus based on the relationship between the speed of sound propagation in a test tube and the Young's modulus. Overall, dynamic testing methods primarily measure the Young's modulus of a material by relating it to certain properties or its structure. Dynamic testing methods can determine the Young's modulus at different temperatures and can also be used to measure the Young's modulus of brittle materials.
[0004] Generally, laminated films exhibit strong brittleness due to the large amount of silica filler they contain. Thin, brittle laminated films are prone to uneven thickness, blistering, and cracks at the cut edges after direct baking, making them highly susceptible to breakage during sample preparation and sampling. Furthermore, conventional Young's modulus sampling methods typically involve cutting samples, and laminated films are prone to edge breakage during this process, affecting the final test results. In addition, many Young's modulus testing devices have minimum sample thickness requirements; lower material thickness can affect the feasibility and accuracy of the test. Moreover, while conventional Young's modulus testing equipment uses tensile testing machines, these machines are prone to breakage in laminated film materials, making the test impossible.
[0005] Therefore, how to solve the problems of uneven film thickness, bubbling, and cracks at the cut edges during the sample preparation process of the laminated film, and ensure the feasibility and accuracy of the test, has become an urgent technical problem to be solved. Summary of the Invention
[0006] In view of the shortcomings of the prior art described above, the purpose of this invention is to provide a method for preparing and testing an additive film sample for an FCBGA packaging substrate, so as to ensure the quality, integrity and feasibility of the sample.
[0007] To achieve the above and other related objectives, the present invention provides a method for preparing an additive film sample for an FCBGA packaging substrate, comprising the following steps:
[0008] Two additive films for FCBGA packaging substrates are provided, each additive film comprising a first film layer, an additive film layer and a second film layer stacked sequentially.
[0009] The first layer of each add-on film is peeled off to expose the add-on film layer, and the two add-on films with the exposed add-on film layer are stacked opposite each other and placed on the substrate to complete the sample pre-stack; or N add-on films for FCBGA packaging substrates are provided, each add-on film including a first film layer, an add-on film layer and a second film layer stacked in sequence, and the N add-on films include a first add-on film, a second add-on film, a third add-on film... and an Nth add-on film, where N is greater than or equal to 3 and N is an integer;
[0010] The first layer of the first and second adhesive films is peeled off to expose the adhesive film layers. The two adhesive films with the exposed adhesive film layers are stacked opposite each other and placed on the substrate to complete the first pre-stack of the sample. The pre-stacked sample is then pressed together for the first time.
[0011] The first layer of the third layered adhesive film is peeled off to expose the layered adhesive film, and the second layer of the sample after the first pressing is peeled off. The exposed layered adhesive film of the third layered adhesive film is stacked with the exposed layered adhesive film of the sample after the first pressing with the second layer removed to complete the second pre-stack of the sample. The pre-stacked sample is then pressed for the second time.
[0012] Repeat the above steps until the Nth layer of adhesive film is pre-stacked to obtain the pre-stacked sample;
[0013] The pre-stacked samples are pressed together and then baked.
[0014] The baked samples were cut using an irregular, staggered cutting method.
[0015] The second film layer on both sides of the cut sample is peeled off to obtain the sample to be tested. The pre-stacked samples are then pressed together and baked.
[0016] The baked samples were cut using an irregular, staggered cutting method.
[0017] The second membrane layer on both sides of the cut sample is peeled off to obtain the sample to be tested.
[0018] Optionally, the step of pressing the pre-stacked samples includes: pressing the pre-stacked samples using a vacuum press.
[0019] Optionally, a laser cutter can be used to cut the baked sample.
[0020] Optionally, the step of cutting the baked sample using an irregularly shaped, offset cutting method includes:
[0021] The upper two layers of the sample after baking are cut once, and the sample after the first cut is flipped over. Based on the flipped sample, the upper two layers of the sample are cut a second time.
[0022] Optionally, the secondary cutting step of the upper two layers of film based on the flipped sample includes:
[0023] Control the starting point position of the second cut, so that the starting point of the second cut is shifted by a fixed length from the starting point of the first cut.
[0024] Optionally, the cutting pattern during the first cut is different from the cutting pattern during the second cut.
[0025] Optionally, the cutting thickness of the first cut is the sum of the thicknesses of the two upper films, and the cutting thickness of the second cut is the sum of the thicknesses of the two upper films after flipping.
[0026] Optionally, before the step of cutting the baked sample using an irregularly shaped, offset cutting method, the following steps are included:
[0027] Place a protective plate on the cutting machine table;
[0028] Alternatively, the laser cutting machine may be one of a UV laser cutting machine, a picosecond laser cutting machine, or a femtosecond laser cutting machine.
[0029] This invention also discloses a method for testing the add-on film for FCBGA packaging substrates, comprising:
[0030] The sample to be tested is prepared by using the sample preparation method described in any one of the above schemes;
[0031] The Young's modulus of the sample to be tested was determined.
[0032] Optionally, the step of testing the Young's modulus of the sample to be tested further includes:
[0033] The sample under test is tested in tensile mode to obtain the stress-strain curve;
[0034] The slope of the straight-line region at the front end of the stress-strain curve is taken as the magnitude of Young's modulus.
[0035] Compared with the prior art, the method for preparing and testing the additive film for FCBGA packaging substrates described in this invention has at least the following advantages:
[0036] The FCBGA thickening film of this invention includes a sample preparation method that involves removing the high-temperature-resistant protective layer by pressing before curing the thickening film. During curing, a vacuum laminator is used to complete the sample curing. After curing, the sample is cut using a laser cutting method. Finally, a mechanical peeling machine is used to peel off the film before Young's modulus testing on a DMA (Dielectric-Determining Mechanism). This reduces sample quality problems caused by bubbling, uneven film thickness, difficulty in release, and edge cracks during sampling, and solves the problem of not being able to test Young's modulus using conventional tensile testing machines. Specifically, the results are as follows:
[0037] 1) Protect the operating platform
[0038] To prevent damage to the operating equipment during parameter exploration and cutting when laser cutting of laminated films, a protective plate is added below the sample layer. The sample is then cut on the protective plate, which reduces the probability of equipment damage during the operation.
[0039] 2) Ensure sampling integrity
[0040] For laminated adhesive films, ordinary cutting methods can easily cause cracks at the edges, affecting the final test results. Laser cutting can maximize the integrity of dimensions during sampling, reduce the size of cracks, and lower the probability of crack occurrence.
[0041] 3) The sample design allows for easy peeling of the film, making operation simple.
[0042] For samples and protective films of the same size, the sample is easily damaged and difficult to peel off during the peeling process. By using an irregular cutting method to create an "S"-shaped size difference between the upper and lower protective films and the sample, the difficulty of peeling is reduced and the sample is guaranteed to be less damaged and contaminated.
[0043] 4) The Young's modulus measurements show good consistency and the test results are more accurate.
[0044] Conventional Young's modulus sampling techniques typically employ cutting methods, resulting in poor sample dimensional stability. After cutting, the sample edges are prone to burrs and noticeable cracks, making sample fabrication more challenging. The sample fabrication method designed in this invention, using a laser cutter, can obtain dimensionally stable, crack-free irregularly shaped samples. For Young's modulus testing, this ensures that the sample is less likely to break during the testing process, leading to more accurate test results. Attached Figure Description
[0045] Figure 1a This is a flowchart of the steps in the method for preparing the laminated film according to the present invention;
[0046] Figure 1b This is a flowchart illustrating the sample preparation and testing procedures for the extended film as described in this embodiment of the invention.
[0047] Figure 2 This is a schematic diagram of the first layer of adhesive film;
[0048] Figure 3 This is a schematic diagram of the second layer of adhesive film;
[0049] Figure 4 A schematic diagram of the sample after the first layer of the first adhesive film has been removed;
[0050] Figure 5 A schematic diagram of the sample after the first film layer is removed from the second layer of the adhesive film;
[0051] Figure 6 This is a schematic diagram of the sample after the laminated adhesive film is stacked.
[0052] Figure 7 Schematic diagram of attaching an adhesive film to a substrate;
[0053] Figure 8 This is a schematic diagram of the first laser-cut sample.
[0054] Figure 9 This is a schematic diagram of the second laser cutting of the sample;
[0055] Figure 10 This is a schematic diagram of the sample after laser cutting;
[0056] Figure 11 This is a schematic diagram of the sample after the film has been peeled off.
[0057] Figure 12 The stress-strain diagram was obtained by testing the Young's modulus of the prepared sample.
[0058] Figure 13 A schematic diagram of a sample made for this invention;
[0059] Figure 14This is a schematic diagram of a sample cut using a conventional cutting method.
[0060] List of reference numerals in the attached diagram:
[0061] 1, 4 Second film layer
[0062] 2.5 Additional Adhesive Film Layers
[0063] 3, 6 First film layer
[0064] 7. Pressing the reinforcing film layer
[0065] 8 substrate
[0066] 9. First cutting position
[0067] 10 Secondary cutting position Detailed Implementation
[0068] The following specific embodiments illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and various details in this specification can also be modified or changed based on different viewpoints and applications without departing from the spirit of this application. It should be noted that, unless otherwise specified, the following embodiments and features in the embodiments can be combined with each other.
[0069] It should be understood that the illustrations provided in the embodiments of this invention are merely schematic representations of the basic concept of the invention. Although the illustrations only show components relevant to the invention and are not drawn according to the actual number, shape, and size of components in implementation, the shape, quantity, and proportion of each component can be arbitrarily changed in actual implementation, and the component layout may also be more complex. The structures, proportions, sizes, etc., shown in the accompanying drawings are only used to complement the content disclosed in the specification for those skilled in the art to understand and read, and are not intended to limit the conditions under which this application can be implemented. Therefore, they have no substantial technical significance. Any modifications to the structure, changes in the proportional relationships, or adjustments to the size, without affecting the effects and objectives that the invention can produce, should still fall within the scope of the technical content disclosed in this application.
[0070] This embodiment provides a method for preparing an additive film sample for an FCBGA (Flip Chip Ball Grid Array) packaging substrate. It should be noted that this invention does not limit the application of the additive film and is applicable to other packaging substrates as well. The specific steps include:
[0071] S101: Provide two layers of additive adhesive film for FCBGA packaging substrate, each of the additive adhesive films comprising a first film layer, an additive adhesive film layer and a second film layer stacked sequentially.
[0072] Specifically, this embodiment provides two laminated films, each laminated film including a first film layer, a laminated film layer and a second film layer stacked sequentially.
[0073] In this embodiment, both the first and second film layers serve as protective layers to isolate and protect the intermediate adhesive layer. Generally, the first film layer is a polypropylene film (OPP film), which is not heat-resistant. The second film layer is a polyethylene terephthalate film (PET film), which has certain heat-resistant properties. The adhesive layer in this embodiment is a material commonly used in encapsulation substrates in the prior art; its specific material will not be detailed here.
[0074] S102: Remove the first film layer of each of the laminated adhesive films to expose the laminated adhesive film layer, and stack the two laminated adhesive films with the exposed laminated adhesive film layer side to side and place them on the substrate to complete the sample pre-stacking;
[0075] Specifically, the first layers of the two adhesive films provided in step S101 are peeled off to expose the adhesive film layer located between the first and second film layers. The exposed surfaces of the two adhesive films with their first layers removed are then stacked face to face, and the stacked adhesive films are placed on the substrate to complete the sample pre-stacking. It should be noted that the first film layer is not resistant to high temperatures, so it is peeled off first to avoid damage from high temperatures in subsequent steps, which would be detrimental to the protection of the adhesive film layer.
[0076] In one embodiment, steps S101 and S102 may further be the following steps:
[0077] S101: Provide N layers of additive adhesive film for FCBGA packaging substrate. Each additive adhesive film includes a first film layer, an additive adhesive film layer and a second film layer stacked in sequence. The N layers of additive adhesive film include a first additive adhesive film, a second additive adhesive film, a third additive adhesive film, ..., an Nth additive adhesive film. N is greater than or equal to 3 and N is an integer.
[0078] S102: Remove the first film layer of the first and second adhesive films respectively to expose the adhesive film layer, and stack the two adhesive films with the exposed adhesive film layer side facing each other on the substrate to complete the first pre-stack of the sample, and press the pre-stacked sample for the first time.
[0079] The first layer of the third layered adhesive film is peeled off to expose the layered adhesive film, and the second layer of the sample after the first pressing is peeled off. The exposed layered adhesive film of the third layered adhesive film is stacked with the exposed layered adhesive film of the sample after the first pressing with the second layer removed to complete the second pre-stack of the sample. The pre-stacked sample is then pressed for the second time.
[0080] Repeat the above steps until the Nth layer of adhesive film is pre-stacked to obtain the pre-stacked sample;
[0081] It should be noted that, in this invention, the number of laminated adhesive films can be selected according to requirements, and this invention does not limit the number of laminated adhesive films.
[0082] S103: Press the pre-stacked samples together and bake them;
[0083] Specifically, the pre-stacked samples from step S102 are pressed together. To prevent air bubbles or uneven film thickness during the pressing process, this embodiment uses a vacuum laminator to press the pre-stacked samples. During the pressing process, because vacuum lamination is used, no air bubbles are generated inside the sample, thus ensuring that uneven film thickness is avoided. After pressing the pre-stacked samples, the pressed samples also need to be baked to ensure that the two adhesive film layers adhere well together.
[0084] S104: The baked sample is cut using an irregularly shaped, staggered cutting method;
[0085] Specifically, the baked sample from step S103 is cut to obtain a sample size suitable for testing. The substrate needs to be removed before cutting.
[0086] To ensure the integrity of the cut sample and avoid cracks at the edges during the cutting process, a laser cutting machine is used to cut the baked sample in this embodiment. Laser cutting can reduce the length and probability of edge cracks in the material. Laser cutting includes UV cutting, picosecond cutting, and femtosecond cutting. UV cutting uses a precision laser cutting device with a 355nm ultraviolet laser. Its principle is to use a high-density, high-energy laser beam to irradiate the material surface, breaking the molecular bonds of the material to form a cut.
[0087] Picosecond cutting operates on the principle of ultrafast laser radiation of picosecond wavelengths. The material absorbs these photons, generating conduction band electrons. These high-energy electrons transfer absorbed energy to the crystal lattice, causing material melting or mechanical damage through energy deposition, thus achieving high-precision micromachining. Picosecond cutting can achieve extremely high peak light intensity with relatively low pulse energy. The ultrashort pulses generated by ultrafast lasers interact with the material for an extremely short time. When the laser pulse width reaches the picosecond or femtosecond range, the influence of molecular thermal motion can be largely avoided, preventing thermal impact on surrounding materials. Therefore, ultrafast laser processing is also known as cold processing. Ultrafast laser "cold processing" reduces melting and the heat-affected zone, resulting in fewer microcracks and better surface ablation quality. The absorption of laser energy is less dependent on the material and wavelength, exhibiting characteristics such as low heat generation, cold ablation, and high precision, making it suitable for precision material machining.
[0088] The principle of femtosecond cutting is that after a femtosecond laser is generated, gaseous, liquid, and solid substances are instantly transformed into plasma under the action of a high-intensity femtosecond laser. The collision of a high-power femtosecond laser with an electron beam can generate X-ray femtosecond lasers, X-ray lasers, and electron-positron pairs. Furthermore, femtosecond lasers can effectively accelerate electrons, allowing for a thousand-fold reduction in the size of accelerators. The interaction of a high-power femtosecond laser with matter can generate a sufficient number of neutrons to achieve rapid ignition of laser-controlled nuclear fusion. When the pulse width (impact time) of laser processing is short enough to be femtosecond... -15 During processing with 1000-second laser pulses, each femtosecond (10^6) laser pulse... -15 A femtosecond laser pulse is focused onto the workpiece being processed. Due to the extremely high frequency of the femtosecond pulse, the amount of material vaporized (etched) each time is small and leaves very quickly. It is precisely because this process is extremely short (femtosecond level) and has an extremely high frequency that the vaporized material does not have enough time to exchange heat with the surrounding material, so it will not affect the surrounding material. That is, it will not produce a "heat affected zone (HAZ)" such as melting, oxidation, or burrs on the surrounding material, thereby achieving precise removal of the area where the material to be removed needs to be removed.
[0089] Laser cutting offers processing characteristics that meet the specific requirements of cutting laminated adhesive materials. Optionally, the laser cutting machine can be a UV laser cutter, a picosecond laser cutter, or a femtosecond laser cutter. During cutting, a protective plate is first placed on the surface of the cutting machine to prevent damage to the machine surface during the laser cutting process. After placing the protective plate, the sample is cut based on the protective plate.
[0090] To ensure easy peeling of the second film layer from the reinforcing film layer after cutting, and to avoid damage to the sample edges during peeling, this embodiment employs an irregularly shaped, staggered cutting method. Specifically, the upper two layers of the baked sample are first cut, and the sample is then flipped over. Based on the flipped sample, the upper two layers are then cut a second time. During the cutting process, the starting point of the second cut is controlled so that it is shifted by a fixed length from the starting point of the first cut.
[0091] Optionally, the cutting patterns during the first and second cuts can be the same or different. In this embodiment, the cutting patterns during the first and second cuts are set to different shapes to obtain different target patterns.
[0092] S105: Peel off the second film layer on both sides of the cut sample to obtain the sample to be tested.
[0093] The second membrane layers on both sides of the cut sample are peeled off to obtain the sample to be tested. Optionally, a membrane peeling machine can be used to peel off the second membrane layers on the sample.
[0094] After sample preparation, this embodiment also provides a method for testing the addendum film for a packaging substrate, which further includes the following steps:
[0095] S106: Prepare the sample to be tested using the above sample preparation method;
[0096] For specific steps, please refer to steps S101 to S105 above, which will not be repeated here.
[0097] S107: Perform Young's modulus testing on the sample to be tested.
[0098] During the testing process, the tensile mode was selected to test the sample, and a stress-strain curve was obtained. The slope of the straight-line region at the front end of the stress-strain curve was taken as the magnitude of Young's modulus. It should be noted that for the testing of the laminated film, the material belongs to the category of polymer research. Young's modulus is the ratio of stress to strain, which measures the ability of a solid material to resist deformation. It does not change with the magnitude of stress and strain. However, during the test, as the stress changes, the measured stress-strain ratio of the sample changes. This is mainly because when the stress is small, elastic deformation occurs, and the deformation can be recovered after the external force is removed. As the stress increases, the material undergoes plastic deformation. At this time, after the external force is removed, the material undergoes permanent deformation that cannot be recovered. Since Young's modulus is also called elastic modulus, the value range of Young's modulus should be limited to the small deformation region, that is, the region where the front end of the curve tends to be a straight line.
[0099] Specifically, the sample is tested in tensile mode, a certain preload force is applied, and it is balanced at a certain temperature for 2 to 5 minutes. The ramp force is adjusted from the current force to 18 N, and the ramp rate is 0.5 to 5.0 N / min. After the test is completed, the stress-strain curve is obtained. The slope value of the straight line region at the front end is the Young's modulus, and the unit is GPa.
[0100] The following detailed description of the preparation and testing methods for the additive film used in FCBGA packaging substrates according to the present invention, with reference to specific embodiments, provides a detailed explanation.
[0101] Example 1:
[0102] This embodiment provides a method for preparing and testing Young's modulus samples of the add-on film for FCBGA packaging substrates. Please refer to the following for the operation procedure. Figure 1b Specifically, it includes the following steps:
[0103] like Figure 2 As shown in Figure 3, the additive adhesive film for the FCBGA packaging substrate has a three-layer structure: the upper layer is the first film layer 3 and 6, the middle layer is the additive adhesive film layer 2 and 5, and the lower layer is the second film layer 1 and 4. Take two pieces of additive adhesive film, peel off the first film layer 3 and 6 on the surface of the additive adhesive film, as shown in Figure 3. Figure 4 , Figure 5 As shown. The exposed adhesive layer 2 and adhesive layer 5 are stacked together. Then, another substrate 8 is taken, and the stacked sample is placed on substrate 8 to complete the sample pre-stacking. Figure 7 As shown.
[0104] After the pre-stacked samples are placed in a vacuum laminator, the samples need to be baked after lamination.
[0105] After the sample has finished baking, substrate 8 is removed. The sample after removing substrate 8 is shown in the image. Figure 8 At this point, the sample contains a second film layer 1, a second film layer 4, and an intermediate laminated adhesive film layer 7. The baked sample is cut using a UV laser cutter. The focal point is adjusted, and the speed is set to 150-130 mm / s, the frequency to 30-50 kHz, the power to 4.0-6.0 W, and the number of cuts is 2-3.
[0106] During cutting, a protective plate is first placed on the machine surface before sample cutting. In this embodiment, sample cutting is irregular-shaped cutting, divided into two stages: First stage: Based on the first cutting position 9, the upper two layers of film are cut, and the cutting thickness is the sum of the thicknesses of the upper two layers of film at this time, such as... Figure 8As shown. After flipping, the second stage: control the starting point position of the secondary cut, so that the starting point of the secondary cut is shifted by a fixed length from the starting point of the primary cut. That is, based on the secondary cut position 10, the film located on the upper two layers at this time is cut, and the cut thickness is the sum of the thicknesses of the upper two layers at this time, as shown. Figure 9 As shown.
[0107] like Figure 10 As shown, the cut sample is placed on a film peeling machine to peel off the film, obtaining the sample to be tested, namely the laminated reinforcing film layer 7. Because this embodiment uses an irregularly shaped, staggered cutting method to cut the sample, both the second film layer 4 and the second film layer 1 have portions that are not adhered to the laminated reinforcing film layer 7. Therefore, peeling can be performed based on these non-adherent portions of the second film layers 1 and 4 and the laminated reinforcing film layer 7. This makes the film easy to peel off and avoids damage to the laminated reinforcing film layer 7. The peeled laminated reinforcing film layer 7 is then used for DMA Young's modulus testing, such as... Figure 11 As shown.
[0108] Figure 11 This is a front view of the test sample obtained using the sample preparation method described in this embodiment. Figure 13 for Figure 11 Top view of the structure. Figure 14 This is a top view of the test sample obtained after cutting in the prior art. (Comparison) Figure 13 and Figure 14 As shown in the schematic diagram of the test sample, existing technologies use sample cutting methods to prepare test samples. This results in unstable sample dimensions, and the sample edges are prone to burrs and obvious cracks, making sample preparation difficult and easily leading to significant deviations in Young's modulus test results, thus compromising the stability and accuracy of the test. The sample prepared using this embodiment exhibits good dimensional stability, effectively reducing the probability of sample cracking. Laser cutting facilitates the fabrication of irregularly shaped samples, enabling comparative analysis of Young's modulus test results for any region within the entire test sample. This ensures high accuracy of test results while achieving comprehensive comparative analysis of regional batch samples.
[0109] The sample prepared in this embodiment was tested in tensile mode. A preload force of 0.8 N was applied, and the sample was balanced at 30°C for 3 minutes. The ramp force was increased from the current force to 18 N, and the ramp rate was 2.0 N / min. After the test, the following results were obtained: Figure 12 The slope of the straight section at the front end of the stress-strain curve shown is the Young's modulus, expressed in GPa. The measured Young's modulus is 5.8 GPa.
[0110] Example 2:
[0111] This embodiment provides a method for preparing and testing the Young's modulus of an additive film for an FCBGA packaging substrate. The operation procedure is the same as described above. Figure 1b It includes the following steps:
[0112] like Figure 2 As shown in Figure 3, the add-on adhesive film for the FCBGA packaging substrate has a three-layer structure: the upper layer is the first film layer 3 and 6, the middle layer is the add-on adhesive film layer 2 and 5, and the lower layer is the second film layer 1 and 4. Take two add-on films, peel off the first film layer 3 and 6 on the surface of the add-on adhesive film, as shown in Figure 3. Figure 4 , Figure 5 As shown. The exposed adhesive layer 2 and adhesive layer 5 are stacked together. Then, another substrate 8 is taken, and the stacked sample is placed on substrate 8 to complete the sample pre-stacking. Figure 7 As shown.
[0113] After the pre-stacked samples are placed in a vacuum laminator, the samples need to be baked after lamination.
[0114] After the sample has finished baking, substrate 8 is removed. The sample after removing substrate 8 is shown in the image. Figure 8 At this point, the sample contains a second film layer 1, a second film layer 4, and an intermediate laminated adhesive film layer 7. The baked sample is cut using a picosecond laser cutter. The focal point is adjusted, and the speed is set to 1500–1800 mm / s, the frequency to 1200 kHz, the power to 10.0 W, and the number of cuts is 3–5.
[0115] During cutting, a protective plate is first placed on the machine surface before sample cutting. In this embodiment, sample cutting is irregular-shaped cutting, divided into two stages: First stage: Based on the first cutting position 9, the upper two layers of film are cut, and the cutting thickness is the sum of the thicknesses of the upper two layers of film at this time, such as... Figure 8 As shown. After flipping, the second stage: control the starting point position of the secondary cut, so that the starting point of the secondary cut is shifted by a fixed length from the starting point of the primary cut. That is, based on the secondary cut position 10, the film located on the upper two layers at this time is cut, and the cut thickness is the sum of the thicknesses of the upper two layers at this time, as shown. Figure 9 As shown.
[0116] like Figure 10As shown, the cut sample is placed on a film peeling machine to peel off the film, obtaining the sample to be tested, namely the laminated reinforcing film layer 7. Because this embodiment uses an irregularly shaped, staggered cutting method to cut the sample, both the second film layer 4 and the second film layer 1 have portions that are not adhered to the laminated reinforcing film layer 7. Therefore, peeling can be performed based on these non-adherent portions of the second film layers 1 and 4 and the laminated reinforcing film layer 7. This makes the film easy to peel off and avoids damage to the laminated reinforcing film layer 7. The peeled laminated reinforcing film layer 7 is then used for DMA Young's modulus testing, such as... Figure 11 As shown.
[0117] The sample was tested in tensile mode with a preload force of 0.8 N, balanced at 30°C for 3 minutes, and the ramp force was adjusted from the current magnitude to 18 N. The ramp rate was 2.0 N / min. The results after the test were as follows: Figure 12 The slope of the straight section at the front end of the stress-strain curve shown is the Young's modulus, expressed in GPa. The measured Young's modulus is 5.8 GPa.
[0118] In summary, during sample preparation, the high-temperature-sensitive protective layer of the extended film of this invention is removed by pressing before curing. During curing, a vacuum laminator is used to complete the sample curing. After curing, the sample is cut using laser cutting. Finally, a mechanical peeling machine is used to peel off the film before Young's modulus testing on a DMA (Dielectric-Determining Mechanism). This reduces sample quality issues caused by bubbling, uneven film thickness, difficulty in release, and edge cracks during sampling, and solves the problem of not being able to test Young's modulus using conventional tensile testing machines. Specific performance is as follows:
[0119] 1) Protect the operating platform
[0120] To prevent damage to the operating equipment during parameter exploration and cutting when laser cutting of laminated films, a protective plate is added below the sample layer. The sample is then cut on the protective plate, which reduces the probability of equipment damage during the operation.
[0121] 2) Ensure sampling integrity
[0122] For laminated adhesive films, ordinary cutting methods can easily cause cracks at the edges, affecting the final test results. Laser cutting can maximize the integrity of dimensions during sampling, reduce the size of cracks, and lower the probability of crack occurrence.
[0123] 3) The sample design allows for easy peeling of the film, making operation simple.
[0124] For samples and protective films of the same size, the sample is easily damaged and difficult to peel off during the peeling process. By using an irregular cutting method to create an "S"-shaped size difference between the upper and lower protective films and the sample, the difficulty of peeling is reduced and the sample is guaranteed to be less damaged and contaminated.
[0125] 4) The Young's modulus measurements show good consistency and the test results are more accurate.
[0126] Conventional Young's modulus sampling techniques typically employ cutting methods, resulting in poor sample dimensional stability. After cutting, the sample edges are prone to burrs and noticeable cracks, making the fabrication of irregularly shaped samples even more challenging. The sample fabrication method designed in this invention, using a laser cutter, can produce dimensionally stable, crack-free irregularly shaped samples. For Young's modulus testing, this method ensures that the sample is less likely to break during the testing process, leading to more accurate test results.
[0127] The above embodiments are merely illustrative of the principles and effects of the present invention and are not intended to limit the invention. Any person skilled in the art can modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by those skilled in the art without departing from the spirit and technical concept disclosed in the present invention should still be covered by the claims of the present invention.
Claims
1. A method for preparing an additive film sample for an FCBGA packaging substrate, characterized in that, Includes the following steps: Two additive films for FCBGA packaging substrates are provided, each of the additive films comprising a first film layer, an additive film layer and a second film layer stacked sequentially. The first film layer of each of the laminated adhesive films is peeled off to expose the laminated adhesive film layer, and the two laminated adhesive films with the exposed laminated adhesive film layer side to side are stacked and placed on the substrate to complete the sample pre-stacking; The pre-stacked samples are pressed together and then baked. The baked sample is cut using an irregularly shaped, staggered cutting method, including: cutting the top two layers of the baked sample once, flipping the sample after the first cut, and then cutting the top two layers of the sample a second time based on the flipped sample. The starting point of the second cut is controlled so that it is shifted by a fixed length from the starting point of the first cut. The thickness of the first cut is the sum of the thicknesses of the top two layers of the sample, and the thickness of the second cut is the sum of the thicknesses of the flipped top two layers of the sample. The substrate needs to be removed before cutting. The second membrane layer on both sides of the cut sample is peeled off to obtain the sample to be tested.
2. A method for preparing an additive film sample for an FCBGA packaging substrate, characterized in that, Includes the following steps: N layers of additive adhesive film for FCBGA packaging substrate are provided. Each layer of additive adhesive film includes a first film layer, an additive adhesive film layer and a second film layer stacked in sequence. The N layers of additive adhesive film include a first additive adhesive film, a second additive adhesive film, ..., an Nth additive adhesive film, where N is greater than or equal to 3 and N is an integer. The first layer of the first and second adhesive films is peeled off to expose the adhesive film layers. The two adhesive films are then stacked with one side of the exposed adhesive film layers facing each other and placed on the substrate to complete the first pre-stack of the sample. The pre-stacked sample is then pressed together for the first time. The first layer of the third layered adhesive film is peeled off to expose the layered adhesive film. The second layer of the sample after the first pressing is peeled off to expose the layered adhesive film. The exposed layered adhesive film of the third layered adhesive film is stacked with the exposed layered adhesive film of the sample after the first pressing with the second layer removed to complete the second pre-stack of the sample. The pre-stacked sample is then pressed for the second time. Repeat the above steps until the Nth layer of adhesive film is pre-stacked to obtain the pre-stacked sample; The pre-stacked samples are pressed together and then baked. The baked sample is cut using an irregularly shaped, staggered cutting method, including: cutting the top two layers of the baked sample once, flipping the sample after the first cut, and then cutting the top two layers of the sample a second time based on the flipped sample. The starting point of the second cut is controlled so that it is shifted by a fixed length from the starting point of the first cut. The thickness of the first cut is the sum of the thicknesses of the top two layers of the sample, and the thickness of the second cut is the sum of the thicknesses of the flipped top two layers of the sample. The substrate needs to be removed before cutting. The second membrane layer on both sides of the cut sample is peeled off to obtain the sample to be tested.
3. The method for preparing a layered adhesive film sample for an FCBGA packaging substrate according to claim 1 or 2, characterized in that, The step of pressing the pre-stacked samples includes: pressing the pre-stacked samples using a vacuum press.
4. The method for preparing an additive film sample for an FCBGA packaging substrate according to claim 1 or 2, characterized in that, The baked samples were cut using a laser cutting machine.
5. The method for preparing an additive film sample for an FCBGA packaging substrate according to claim 1, characterized in that, The cutting pattern during the first cut is different from the cutting pattern during the second cut.
6. The method for preparing an additive film sample for an FCBGA packaging substrate according to claim 1 or 2, characterized in that, Before cutting the baked sample using the irregular offset cutting method, the following steps are included: Place a protective plate on the cutting machine table; The baked sample is placed on the protective plate.
7. The method for preparing an additive film sample for an FCBGA packaging substrate according to claim 4, characterized in that, The laser cutting machine is one of a UV laser cutting machine, a picosecond laser cutting machine, or a femtosecond laser cutting machine.
8. A method for testing the add-on film for FCBGA packaging substrates, characterized in that, include: The sample to be tested is prepared by using the sample preparation method according to any one of claims 1 to 7; The Young's modulus of the sample to be tested was then measured.
9. The method for testing the add-on film for FCBGA packaging substrate according to claim 8, characterized in that, The step of performing Young's modulus testing on the sample to be tested also includes: The sample under test was tested in tensile mode to obtain stress-strain curves; The slope of the straight-line region at the front end of the stress-strain curve is taken as the magnitude of Young's modulus.
Citation Information
Patent Citations
Method for testing the peel strength of solid electrolyte membrane
CN110987792A
Optical fiber outer coating layer in-situ modulus testing method
CN111122321A